2018
DOI: 10.1111/pce.13191
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underpinning phosphorus‐use efficiency in rice

Abstract: Orthophosphate (H PO , Pi) is an essential macronutrient integral to energy metabolism as well as a component of membrane lipids, nucleic acids, including ribosomal RNA, and therefore essential for protein synthesis. The Pi concentration in the solution of most soils worldwide is usually far too low for maximum growth of crops, including rice. This has prompted the massive use of inefficient, polluting, and nonrenewable phosphorus (P) fertilizers in agriculture. We urgently need alternative and more sustainabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 163 publications
(340 reference statements)
3
63
0
Order By: Relevance
“…Similarly, there was no response of photosynthetic rate to N and P fertilization in understorey species of a tropical plantation (Zhu, Lu, & Mo, ) or in response to P addition in lowland tropical forest understorey seedlings after 10 years of P fertilization (Pasquini & Santiago, ). The results, combined with LMA results, also agree with studies of several crop species which demonstrated that photosynthesis is far less sensitive to fertilization than leaf growth (Assuero et al, ; Chiera et al, ; Dissanayaka et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, there was no response of photosynthetic rate to N and P fertilization in understorey species of a tropical plantation (Zhu, Lu, & Mo, ) or in response to P addition in lowland tropical forest understorey seedlings after 10 years of P fertilization (Pasquini & Santiago, ). The results, combined with LMA results, also agree with studies of several crop species which demonstrated that photosynthesis is far less sensitive to fertilization than leaf growth (Assuero et al, ; Chiera et al, ; Dissanayaka et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Under P deficiency, photosynthesis is generally reduced (Turnbull, Warren, & Adams, 2007) due to feedback inhibition resulting from reduced leaf growth (Dissanayaka et al, 2018) or because orthophosphate (Pi) in the cytosol becomes limiting (Warren, 2011). Plants also tend to increase their leaf mass per unit area (LMA; Chiera, Thomas, and Rufty (2002) and increase their photosynthetic P-use efficiency (Hidaka & Kitayama, 2009) when P supply is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate forms a major component of fundamental biomolecules such as nucleic acids, adenosine phosphates and phospholipids. Ignoring stored vacuolar phosphorus, cellular phospholipids can account for up to a third of organic phosphorus in cells (in the order of RNA > phospholipids > phosphate-esters > DNA > phosphorylated proteins) and therefore represent a major proportion of the phosphorus budget [32,33] . Adaptive metabolic responses that release these stores can make a major contribute to plant adaption to growth under lowphosphorus conditions and represents a target for improving crop phosphorus use efficiency.…”
Section: Membrane Lipid Remodeling: a Strategy To Improve Crop Phosphmentioning
confidence: 99%
“…3). Metabolic adaptation and membrane remodeling enables plants to adapt to extremely low-phosphorus environments [33,34] . Yet the fundamental understanding of the processes underpinning membrane lipid exchange in crops remains limited.…”
Section: Membrane Lipid Remodeling: a Strategy To Improve Crop Phosphmentioning
confidence: 99%
“…Remobilization of P-containing metabolites is considered as an important strategy for plants adaption to P deficiency [15]. Under P-limiting conditions, P-containing metabolites, such as nucleic acid, phospholipids and phosphorylated sugars, can be scavenged to release Pi and maintain P homeostasis in plant cells [60]. It has been shown that phosphorylated sugars are reduced by P deficiency in various plants, such as Arabidopsis [37], barley [40], white lupin (Lupinus albus) [61] and Populus cathayana [62].…”
Section: Scavenging Of Pi From P-containing Metabolites During P Defimentioning
confidence: 99%